The development of tourism in Russia based on the event - events - V. A. Zhukov (Управление)
The possibility of increasing tourist traffic to the Russian regions based on the development of event tourism has considered. The advantages of developing event events for the host region have shown. The following types of tourism have highlighted: festivals, carnivals, parades, celebrations; conferences, forums, symposia, round tables; seminars, trainings, advanced training courses; sport competitions; concerts, film screenings, theater productions; anniversaries, weddings, celebrations; exhibitions, fairs, trade shows, presentations, business openings, receptions, events related to brand promotion, etc. The problems of modern development of inbound foreign tourism in Russia have analysed: the decline in the share of foreign tourists, the independent organization of recreation in Russia without the involvement of travel companies, the short period of stay in the country. It has revealed that the main source of development of Russian tourism is currently domestic tourism. This fact indicates the prospects for the development of the event market to attract tourists to the Russian regions. On specific examples from the experience of the сarrying World Cup 2018, the positive impact of event tourism on the growth of profitability in the sphere of hotel services has shown. An analysis of the carrying World Cup on the example of St. Petersburg also has revealed, that not all regions of Russia showed an expected increase in profitability. This сircumstance testifies the need for serious marketing research of consumer demand for holding event events. A positive experience in the development of tourism in certain Russian regions - in St. Petersburg and the Vladimir region, which actively use various kinds of festivals and holidays to attract Russian and foreign tourists in order to increase revenues of regional hotels and tourism industry and replenish the local budget, has adduced.